Non-invasive Electroencephalography Method Development and Validation using Carbamazepine (Asian Journal of Pharmaceutics (AJP), 2019)
Context: Recording of neurophysiological properties in a rodent model by stereotaxic surgery is well known, whilethe non-invasive method used to investigate the neurophysiological effects of studied using carbamazepine (CBZ).Aims: The effects of CBZ electrical activity of the brain recorded using a non-invasive technique and validatedby an experiment involving stereotaxic surgery procedure are described in this paper. Settings and Design: Tominimize painful procedures in rodents, an affordable technique was developed to record electroencephalogram(EEG) in the rodent model, and to the test drug molecules screened without giving any anesthetic agent.Methods and Materials: The present invention provides a disposable plastic foam EEG leads relates to a EEGcomponent device for recording rat brain physiological changes in the form of EEG. This study was performedto quantify the pharmacodynamic properties of the CBZ. Rat surgery involving stereotaxic experiment used forvalidation process is described for the non-invasive method in this paper. Statistical Analysis Used: Paired ttest used to calculate the differences in different EEG bands. Results: EEG analysis showed CBZ significantlyincreased in the delta and theta power and no effects on other the frequencies of the EEG. Similar observationswere found in the invasive method of EEG in rats. Clinical and neurophysiological assessment using the simple,inexpensive technique of EEG observed. Conclusions: The results have shown CBZ induced a significant increasein slow activity waves represented by delta and theta waves. Administration of the carbamazepine in rats detectedmajor neurological changes in the form of EEG and the technique of non-invasive EEG measurement found to bea useful tool to detect changes in the EEG.